Malignant Peripheral Nerve Sheath Tumor (MPNST) Arising in Diffuse-type Neurofibroma. (September 2015) - Schaefer, Inga-Marie; Fletcher, Christopher D.M.
<x xml:space="preserve">Abstract</x> Diffuse-type neurofibroma, an uncommon variant of neurofibroma, is associated with neurofibromatosis type 1 in ∼60% of cases. Typically presenting in young adults as ill-defined plaque-like dermal/subcutaneous thickening, most cases are located on the trunk or the head and neck region. Malignant transformation is extremely rare. Nine cases of malignant peripheral nerve sheath tumor (MPNST) arising in diffuse-type neurofibroma (identified in consult files) are described, including clinicopathologic features and follow-up. Five patients were male and 4 female, aged 31 to 59 years (median 49 y). All diffuse-type neurofibromas contained Meissner corpuscles, with tumor sizes ranging between 3.6 and 45 cm (median, 7.4 cm). Five patients had a clinical history of neurofibromatosis type 1, and 1 had Klippel-Trénaunay-Weber syndrome. Six tumors arose on the trunk and 1 each on the leg, arm, and scalp. Increased cellularity, nuclear atypia, and mitoses (range, 1 to 63/50 high-power fields) indicated transition to MPNST, classified as low grade in 5, intermediate to high grade in 1, and high grade in 3 cases, 1 of which exhibited heterologous angiosarcomatous differentiation. S-100 expression was quite strong and diffuse in the neurofibroma components and less extensive or weaker in MPNST. Follow-up, available for all patients (median, 80.5 mo, except 1 recent case), revealed that 1 patient developed local recurrence after 9 months; 1 with metastases at the time of initial diagnosis died 1 month after tumor resection. All other patients were alive without evidence of disease at 15 to 145 months (median, 83 mo). Diffuse-type neurofibroma may show transformation to MPNST in very rare instances. It is important to be aware of possible malignant change, requiring thorough sampling of resection specimens and long-term clinical follow-up of patients with unexcised lesions.